-6(v+3)+3v+7=6v+7

Simple and best practice solution for -6(v+3)+3v+7=6v+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(v+3)+3v+7=6v+7 equation:


Simplifying
-6(v + 3) + 3v + 7 = 6v + 7

Reorder the terms:
-6(3 + v) + 3v + 7 = 6v + 7
(3 * -6 + v * -6) + 3v + 7 = 6v + 7
(-18 + -6v) + 3v + 7 = 6v + 7

Reorder the terms:
-18 + 7 + -6v + 3v = 6v + 7

Combine like terms: -18 + 7 = -11
-11 + -6v + 3v = 6v + 7

Combine like terms: -6v + 3v = -3v
-11 + -3v = 6v + 7

Reorder the terms:
-11 + -3v = 7 + 6v

Solving
-11 + -3v = 7 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
-11 + -3v + -6v = 7 + 6v + -6v

Combine like terms: -3v + -6v = -9v
-11 + -9v = 7 + 6v + -6v

Combine like terms: 6v + -6v = 0
-11 + -9v = 7 + 0
-11 + -9v = 7

Add '11' to each side of the equation.
-11 + 11 + -9v = 7 + 11

Combine like terms: -11 + 11 = 0
0 + -9v = 7 + 11
-9v = 7 + 11

Combine like terms: 7 + 11 = 18
-9v = 18

Divide each side by '-9'.
v = -2

Simplifying
v = -2

See similar equations:

| 2a-(a+3)+3= | | 2(v+8)+5v=37 | | 9=5(u-3)+3u | | 28=4(w+6)-6w | | 1/9a=6 | | 6(-2-x)=-5(x+3) | | 5x-4-3x=14 | | -4=n | | 4e^3x+2=110 | | 10(s-4)=-132 | | 4e^3x+2=20 | | 10(s-4)=3 | | 10/3(10) | | 4e^3x-2=110 | | 2/3=7/x-4 | | -7-15x=23 | | 0.2+x=3 | | 2x+3y+6z=98 | | 60x=-32 | | 82=14+2x | | -5(7x+10)=-295 | | 3/4p=114 | | 26/x=13/8 | | y=x^2-17/2 | | 2c+5=3c | | 17x-4=4(4x+5)-16 | | 2c+5=8c | | 4c+6=6c | | 4c+6=6 | | 10x(8x^3+1)=0 | | log(x/5)=3 | | x+9=8+4 |

Equations solver categories